Expansão Urbana E Serviços De Saneamento Básico: Uma Análise Do Bairro Jutaí Em Santarém/PA - (:unkn) unknown (UNIVERSIDADE FEDERAL DO OESTE DO PARÁ, 2024)
Disorderly urban expansion brings with it a series of problems for the city space, including the absence or inefficiency of basic sanitation services, which in turn causes social and environmental problems. Therefore, this work aims to analyze the supply of basic sanitation in the Jutaí neighborhood in Santarém/PA, which in recent years has been the scene of unplanned urban expansion. To construct the work, a bibliographical survey and field research were used with the application of a questionnaire and direct observation. The results demonstrated a major deficiency in the basic sanitation service, especially in areas where the low-income population is concentrated. It is concluded that one of the improvement alternatives would be investments that cover all services, such as urban drainage, sewage, solid waste management and adequate water supply.
Keywords: Expansão Urbana; Saneamento Básico; Planejamento Urbano; CIÊNCIAS HUMANAS